The Fundamental Problems of Security and National Interests in the Changing World under the New Paradigms of Allied Relationships - Gevondyan, Alen (YSU Journal of International Affairs, 2023)
The current stage of confrontation between the West and the Russian Federation is unprecedented in terms of its scale, depth, and nature. This situation increases the role and importance of the international security assurance mechanisms, organizations and the international law. The confrontation changes the global order and balance of power which has been established after the collapse of the USSR.In the South Caucasus the shift of the balance of power occurred as a result of 2020 War. This is evidenced by the ongoing tensions around the Republic of Armenia and Artsakh, as well as the local military provocations. In this context the Article discusses the issues of the RA national interests, the factors that affect them in the current situation and highlights the importance of resource security in formulating the national security agenda.In the presented study, an important role is given to the security risks and choice of military paradigm, which should reflect the power balance that is not yet established in the region.In this article, it is assumed that in the process of ensuring the security of the RA the role of allied relations with the Russian Federation should be carefully and realistically assessed based on the reciprocal interests and realism.
Keywords: balance of power; national interest; the Republic of Armenia; Azerbaijan; CSTO; allied relations; the South Caucasus; political-military capabilities; collective security; security risk